E-Appraisal system / Tan Lai Yen - Tan, Lai Yen (2005)
This project is described about E-Appraisal system in university malaya. lt is a web-based system that enables staffs being evaluated by their supervisor, This system is targeted to academic staff and also technical staff in addition to the frontend store that serves to provides the staff to insert personal details and supervisor to do evaluation. This system will also provide for the mean of maintaining the site by authorized administrators. A research has been carried out to the similar existing system. several types of operating system, programming languages and database. After comparing a few tools, Windows XP has been chosen as the operating system for this system. Database will be developed by using Microsoft Access while the programming language environment will be ASP. Functional requirement and non-functional requirement are discussed. Functional requirement is important to show how the system interacts with user and modules involve in the system. Non-functional requirement is important in produced a system with security, usability, reliability and etc. However, hardware and software requirement also play important role. The system functionality, database and interface has been design and are shown to make the user has a clearer picture of the system.